Tears Behind the Closed Doors: A Logistic Analysis of Domestic Violence Against Women in West Bengal, India - Biswas, Priyanka (Crime & delinquency, 2025)
In this present study, the focus has been given to excavating the generalities of domestic abuse against women in the Indian state of West Bengal and understanding the possible determinants. The study findings revealed that 69.68% of study respondents throughout Bengal often experienced any form of domestic violence in their lifetime. Mostly the traditional patriarchal structure that governs Bengal’s society endorses vulnerability among the ever-married women in the family environment, yet some other determinants viz. socio-demographic, socio-cultural as well as situational factors are significantly associated with the victimization of domestic abuse among women in Bengal’s society. This study aims to contribute to society and might help policymakers to address this societal issue more efficiently.